FIGURE 48 in The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago - Shamshev, Igor V.; Sinclair, Bradley J.; Khruleva, Olga A. (Zenodo, 2020)
FIGURE 48. Rhamphomyia (Pararhamphomyia) ursinella Melander, male habitus, lateral view. : Published as part of Shamshev, Igor V., Sinclair, Bradley J. & Khruleva, Olga A., 2020, The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago, pp. 1-75 in Zootaxa 4848 (1) on page 46, DOI: 10.11646/zootaxa.4848.1.1, http://zenodo.org/record/4406987